Pengaruh Diversifikasi Portofolio, Market Timing, dan Fund Manager Skill Tehadap Kinerja Reksa Dana Saham di Indonesia - Ardiyansyah Prawirautama Ali; Marlinda Ina; Maria Yovita R. Pandin (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The investigation explores how spreading investments across assets, predicting market shifts, and the talents of fund leaders shape the results of stock-based mutual funds in Indonesia. Amid a fast-paced and rivalrous financial market scene, the achievements of these funds hinge on the approaches used by their investment overseers. Spreading out holdings across different shares lowers potential losses, whereas spotting the best market entry and exit points showcases a leader's savvy. Meanwhile, the proficiency of fund managers highlights their insight, background, and thoughtful moves to boost portfolio gains. Employing a numerical strategy, the work draws on secondary info from official performance summaries of OJK-approved stock mutual funds during a set timeframe. Fund outcomes are mainly judged using Jensen’s Alpha, and insights are drawn through multi-variable linear modeling to see the weight of each factor on performance.Findings show that asset spreading and market prediction skills have a beneficial but minor role in fund outcomes. However, manager abilities deliver a strong and meaningful boost, suggesting that the wisdom and track record of investment heads are central to stock mutual fund triumphs in Indonesia. This points to the value of expert managers for solid portfolio handling, plus the push to refine spreading and timing tactics that better match evolving market trends.